Human-dog trust and cohesion within French military canine teams - Michenaud, Stéphanie; Bovet, Dalila; Lamour, Thierry; Laguette, Vanessa (Military psychology, 2024)
Studies on the relationships and interactions within human-dog teams in the French Army are scarce. In order to better understand this subject, a qualitative exploratory study was undertaken by conducting semi-structured interviews with dog handlers ( = 16). The interviewees work in the French Army. They are specialized in the detection and neutralization of individuals or explosives. Thematic analysis identified different themes: trust within the team, doubts, interspecific cohesion, and care provided to the dogs. The results highlight the importance of trust within the canine team. It is conceived as a dynamic, constructed process, based on experience, and involving both members of the team. It emerges that trust arises from individual, relational, technical, and experiential factors: the bonds formed, knowledge of one's dog, difficulties related to technical aspects, the reliability of the dog following training, and mission successes. Kindness, support, and mutual protection are also important criteria. A form of interspecific cohesion is envisaged by experienced handlers when affection, knowledge, reliability, mutual assistance, and support are present.